A rational blueprint for the design of chemically-controlled protein switches - Sailan Shui (Nature Portfolio, 2021)
Small-molecule responsive protein switches are crucial components to control synthetic cellular activities. Here, we present a computational protein design strategy to repurpose drug-inhibited protein-protein interactions into OFF- and ON-switches active in cells.